GLOBAL FOOD TRADE AND ITS SOCIOECONOMIC IMPLICATIONS (International Journal of Food and Nutritional Sciences, 2022)
Global food trade plays a pivotal role in ensuring food security, economic growth, and societal well-being worldwide. This research article delves into the complex web of global food trade, analyzing its socioeconomic implications on various stakeholders, from producers to consumers, and its broader impacts on the global economy. Through a multidimensional approach, this study explores the benefits and challenges associated with food trade, including its impact on food availability, affordability, and the livelihoods of farmers and laborers. Furthermore, it discusses the environmental consequences and the potential for international cooperation in addressing the emerging issues within this intricate system.